Assessment of the French nuclear energy system – A case study. (July 2020) - Velasquez, Carlos E.; e Estanislau, Fidéllis B.G. L.; Costa, Antonella L.; Pereira, Claubia
Abstract: The country with the highest nuclear power contribution to its energy matrix is France with 72.28%. The French nuclear history reveals that they trust in reprocessing option since an early stage of the nuclear power plants. Therefore, this work is devoted to studying the two options of a fuel cycle, i.e., Open Fuel Cycle (OFC) and Closed Fuel Cycle (CFC) for this country and the economics of each scenario. The assessment begins using the MESSAGE, since the first official registration by the International Atomic Energy Agency (IAEA), which is in 1970 and tries to follow the model until 2016. After that, the MESSAGE adjusts the energy planning to fit best until 2034 remaining the nuclear activity in this country. The results show the best reactor option to supply 50000 MWyr until 2034 using the two fuel cycle models. Finally, it is shown the amount of resources needed to maintain the nuclear power industry in France and justify the French option of the fuel cycle based on the economic results. The results show the use of nuclear resources taking advantage of a closed fuel cycle. The idea is to show the sustainability of a closed fuel cycle, applying this methodology to countries in nuclear development with a different scenario. Highlights: Open Fuel Cycle (OFC) and Closed Fuel Cycle (CFC) choice. The assessment has been done using the MESSAGE. It shows the sustainability of a closed fuel cycle.